Biomarkers to guide the use of antibiotics for acute exacerbations of COPD (AECOPD): a systematic review and meta-analysis - George Hoult; David Gillespie; Tom M. A. Wilkinson; Mike Thomas; Nick A. Francis (BMC Pulmonary Medicine, 2022)
Abstract Background Antibiotics are frequently prescribed for acute exacerbations of COPD (AECOPD) even though most do not have a bacterial aetiology. Biomarkers may help clinicians target antibiotic use by identifying AECOPD caused by bacterial pathogens. We aimed to summarise current evidence on the diagnostic accuracy of biomarkers for detecting bacterial versus non-bacterial AECOPD. Methods We searched Embase and Medline using a search strategy including terms for COPD, biomarkers and bacterial infection. Data regarding diagnostic accuracy for each biomarker in predicting bacterial cause of exacerbation were extracted and summarised. We used to QUADAS-2 tool to assess risk of bias. Results Of 509 papers identified, 39 papers evaluating 61 biomarkers were eligible for inclusion. Moderate quality evidence was found for associations between serum C-reactive protein (CRP), serum procalcitonin (PCT), sputum interleukin (IL)-8 and sputum tumour necrosis factor alpha (TNF-α), and the presence of bacterial pathogens in the sputum of patients with AECOPD. Having bacterial pathogens was associated with a mean difference (higher) CRP and PCT of 29.44 mg/L and 0.76 ng/mL respectively. There was inconsistent or weak evidence for associations between bacterial AECOPD and higher levels of sputum IL-1β, IL-6, myeloperoxidase (MPO) and neutrophil elastase (NE). We did not find any consistent evidence of diagnostic value for other biomarkers. Conclusions There is moderate evidence from heterogeneous studies that serum CRP and PCT are of value in differentiating bacterial from non-bacterial AECOPD, and little evidence for other biomarkers. Further high-quality research on the role of biomarkers in identifying bacterial exacerbations is needed.